PERSEPSI MENGENAI WAJAR DAN BENAR DALAM PENYAJIAN LAPORAN KEUANGAN ENTITAS SYARIAH - Nur Hisamuddin; Eka Ayu Hilda Pricilia (Universitas Jember, 2013)
Presentation of financial statement from a Shariah entity is an accountability form which made by the entity to be informed the stakeholders-were associated to the entity. This study aims to find out the perceptions of the parties-were associated to shariah accounting or shariah entity about fair dan true in financial statement presentation of shariah entity. This study is a qualitative research with descriptive data and triangulation analysis. The kind of data in this study is primary data which get from direct interview. The result of this study show that there are some senses about using fair and true terminology, which in compilate and present a financial statement for shariah, fair and true must be used together in order to obtain information that fit with event based on agreement, without manipulation information, and without disobeying the rule of Allah SWT. It was shown by the perceptions from the informants in research proccess. This study can be the refference for standard maker in repairing the existence standard or for academicians, practicians, and Islamic teachers as the first step to re-examine the existence standard. Keywords: Perception, presentation, financial statement, shariah entities, fair, true.